Job satisfaction among school nurses - Zborowska-Dulat, Agnieszka; Uchmanowicz, Izabella; Manulik, Ewa; Manulik, Stanisław (Journal of Education, Health and Sport, 2018)
Introduction Job satisfaction among Polish nurses is a significant predictor of the quality of health care provided. A school nurse is a specialist who improves student well-being, promotes health behaviours, advances academic and life success, thus, high levels of motivation and job satisfaction are indispensable to manage this role. Aim The aim of the research was to assess the factors affecting job satisfaction among school nurses. Material and methods The study was conducted among 125 nurses working in Polish schools. Sociodemographic data were obtained using an original questionnaire developed by the authors. The level of job satisfaction was assessed on the basis of the Satisfaction with Work Questionnaire (SPP). Results The mean age of the group studied was 52.7±7.2 years. 93.6% of the respondents had a work experience exceeding 15 years, 42.3% were medical vocational college graduates. Analysis of the SPP questionnaire showed that the group surveyed obtained an average of 5.0±1.0 points (min.2.8, max.7.0). Higher SPP scores were observed in the group of nurses with shorter job seniority (p<0.001), provided with computer equipment (p≤0.001), involved in the implementation of educational programs (p=0.007), and in those who exchanged information about the health needs of a given student with his/her tutor (p=0.002). A statistically significant relationship was shown between the SPP and the number of disabled students being looked after a nurse (R=0.255, p=0.006). Conclusion School nurses are characterized by a high level of job satisfaction. The vast majority of school nurses studied are women getting close to retirement age. There is a need for further research that will include larger study groups from across the country.